HUBUNGAN ADAT MELAYU DENGAN PENDIDIKAN AGAMA ANAK DALAM KELUARGA - Khairuddin Tambusai (Prodi Pendidikan Agama Islam STAIN Mandailing Natal, 2021)
This research is meant to reveal 1) the application of Malay customs among the community, 2) the implementation of child religious education among the Malay community, 3) the Malay custom of relating to child religious education for the community. The respondents were determined as many as families and the instruments of the data gathering used are interviews and questionnaires. After the data is collected, it will be analyzed using a statistical approach. The results of the research carried out are as follows: 1) After carrying out observations and research, the conclusions show that Malay customs make a positive contribution to society. And these customs can be used as a medium in educating children's spirituality, 2) Through hypothesis testing and a questionnaire data through the table, the conclusion is that the hypothesis test carried out using product moment analysis obtained an r value of 0.431 while r table of 0.232 at a significant level of 5% (0.05) thus r arithmetic > r table this means that there is a relationship between Malay customs and children's religious education, 3) The results of the calculation of r arithmetic product moment by looking at the table r interpretation of r arithmetic worth 0.431 are between 0.400 - 0.700 would mean that between Malay customs and child religious education have an influence with a moderate category (enough).